Reaktualisasi Hakikat Profesi Guru: Analisis Tantangan Disrupsi dan Strategi Penguatan Kompetensi di Era Digital - Ali Maulida; Samsuddin; Indri Machtifaliandri; Siti Zulfah Tri Wardah (Al-Kindi, 2026)
Teachers are a central element in the implementation of education and play a strategic role in shaping the quality of human resources, particularly amid the challenges of the digital era and globalization. Teacher professionalism is not only demanded in terms of pedagogical competence but also in ethical commitment, moral responsibility, and a strategic role in shaping students’ character. This study aims to analyze the essence of the teaching profession from normative and conceptual perspectives, examine the position of teachers as strategic agents of national education, and explore teacher professionalism and its multiple roles in the context of contemporary education. This study employs a qualitative method with a literature review approach by analyzing normative, conceptual, and regulatory sources relevant to the teaching profession. The findings indicate that professional teachers possess strong juridical and conceptual foundations, and within the perspective of Islamic education, they are understood integratively through their roles as nurturers, instructors, and educators of moral conduct. Teachers do not merely function as transmitters of knowledge but also serve as moral and spiritual guides who play a vital role in shaping character and civilization. In the era of digitalization and globalization, teacher professionalism faces challenges related to technological adaptation and shifts in social values; however, the role of teachers remains irreplaceable in instilling values, ethics, and character in students. This study concludes that strengthening teacher professionalism that is adaptive to contemporary developments and grounded in ethical and moral values is a fundamental prerequisite for the realization of quality, character-based education oriented toward holistic human development.